Field notes contributed by Douglas C. Harr, June 1, 1982 - Harr, Douglas C.et al (1982)
Field notes were contributed by Douglas C. Harr and other observers. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1982. Epson - sheet feed